TANGGUNG JAWAB SINGLE PARENT ATAS KESEJAHTERAAN ANAK DI ERA COVID-19 MENURUT UNDANG-UNDANG NOMOR 4 TAHUN 1979: The Responsibility of Single Parents for the Welfare of Children in the Era of Covid-19 According to Law Number 4 of 1979 - Adinda Febrini Shalshalillah Rianto; Wahyuni Retnowulandari (AMICUS CURIAE, 2024)
In this Covid-19 era, children are one of the groups of people who are vulnerable to being exposed to the corona virus or its physical and non-physical impacts. In the Legislation, children are also protected by law and their welfare is guaranteed as in Indonesian Law Number 4 of 1979, both parents as part of society, must contribute to maintaining the welfare of children, including single parents. Then what about the responsibilities and efforts of single parents for the welfare of their children in the Covid-19 era? The research uses normative type with the nature of research descriptive analysis with deductive thinking method. The results of the study found the low responsibility and efforts of single parents in fulfilling children's welfare in the Covid-19 Era.